2020
DOI: 10.3390/foods9081122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound Treatments on Tenderness and In Vitro Protein Digestibility of New Zealand Abalone, Haliotis iris

Abstract: Canned pāua, Haliotis iris, is a premium New Zealand product that is exported to Asia. The objective of this research was to investigate the effects of ultrasound treatments on pāua texture, microstructure and in vitro protein digestibility. Whole pāua meat was ultrasound-treated (20 kHz, 464 ± 9 W) for 5 min in water (with or without subsequent soaking in water at 4 °C for 24 h) or ultrasound-treated in 1% actinidin enzyme solution. Post-treatment cooking of canned pāua was done in a water retort at 116 °C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Thawing loss was determined as previously described [ 18 ]. Before thawing, the fish sausage was accurately weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Thawing loss was determined as previously described [ 18 ]. Before thawing, the fish sausage was accurately weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound can promote protein hydrolysis by inducing alterations in protein structure, resulting in the exposure of enzyme cleavage sites and thereby increased protein digestibility [117]. Bagarinao et al (2020) reported that raw ultrasound-treated samples (in water or enzyme solution) showed degradation of the muscle fibers and exhibited an expansion of the extracellular spaces [118].…”
Section: Ultrasound Treatmentsmentioning
confidence: 99%
“…obvious in samples ultrasonicated in an enzyme solution [118]. The main method to improve protein digestion with ultrasound treatment is to soak the meat in water and apply ultrasound, which can cause cavitation effects leading to muscle myofilament collapse, a reduction in the myofibrillar protein size, and hydrolysis of the meat protein (Fig.…”
Section: Ultrasound Treatmentsmentioning
confidence: 99%
“…Dried shrimp are unpopular with the elderly, children, and others with weak chewing abilities, because they are hard and difficult to chew 6‐8 . Many previous studies have shown that meat jerky with high hardness tends to be difficult to digest, whereas digestibility significantly increases after tenderization 9‐12 . Therefore, it is essential to explore methods of tenderizing dried shrimp to improve its chewiness and digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Many previous studies have shown that meat jerky with high hardness tends to be difficult to digest, whereas digestibility significantly increases after tenderization. [9][10][11][12] Therefore, it is essential to explore methods of tenderizing dried shrimp to improve its chewiness and digestibility.…”
Section: Introductionmentioning
confidence: 99%